PENGARUH BELANJA TRANSFER KE DAERAH DAN DANA DESA (TKDD) TERHADAP KETIMPANGAN PEMBANGUNAN DI INDONESIA - Akhadi, Iman (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research was conducted on the topic of the Influence of Regional Transfer and Village Fund Expenditure as government spending instruments in the state budget on Development Inequality in Indonesia. The study utilized Regional Transfer and Village Fund Expenditure (TKDD) data as the independent variable. Meanwhile, the dependent variables were the Regional Disparity Index (Williamson Index) and the Gini Ratio as representations of regional inequality in Indonesia. The data used consisted of panel data, including TKDD expenditure, per capita GRDP, and the population of each province in Indonesia from 2017 to 2021. The research employed a quantitative method using panel data regression analysis (Pooled data). Based on the LM Test results, the Random Effect Model was found to be better than the Common Effect Model for estimating the regression model between TKDD and the Williamson Index (IW) variables. Meanwhile, the best model for estimating the regression model between TKDD and the Gini Index (IG) variables was the Fixed Effect Model after conducting the Chow Test and Hausman Test. Regression testing results indicated that the TKDD variable had a negative and non-significant relationship with the IW variable (development inequality). This is evident from the coefficient value of -0.101798 and a probability value of 0.6012 (greater than 0.05), meaning it is not significant. Similarly, the regression results between the TKDD variable and the IG variable showed a coefficient value of -16477.71 and a probability value of 0.1410 (greater than 0.05), indicating non-significance.